1986
DOI: 10.1002/1097-0142(19860701)58:1<52::aid-cncr2820580110>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The relation of susceptibility to and biologic behavior of thyroid epithelial cell cancer to HLA-DR1

Abstract: Fifty-two patients with thyroid epithelial cell cancer were studied for evidence of association with human leukocyte antigens (HLA). Twenty-eight patients (53.8%) and 19.4% of 160 controls were HLA-DRI-positive, conferring a relative risk of 4.85 (x2 = 21.3, P < 0.0001). HLA-DRl was increased in all histologic types of thyroid cancer. Interestingly 10 of 12 patients with metastatic disease were DR1-positive compared to 18 of 41 patients without metastases (relative risk = 6.1, xz = 4.7, P < 0.05). This study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
1
19
1
1
Order By: Relevance
“…HLA antigens have been associated with well differentiated thyroid carcinoma [7,9,11,13,16]. However no associations were found in some earlier studies [12,14,15].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…HLA antigens have been associated with well differentiated thyroid carcinoma [7,9,11,13,16]. However no associations were found in some earlier studies [12,14,15].…”
Section: Introductionmentioning
confidence: 92%
“…The association of thyroid carcinoma with HLA alleles has been studied by several investigators [7][8][9][10][11][12][13][14][15][16][17]. HLA antigens have been associated with well differentiated thyroid carcinoma [7,9,11,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports support the association between different alleles of HLA and thyroid carcinoma in different populations [7][8][9][10][11][12][13][14][15][16][17]. However different results have also been reported [12,14,15].…”
Section: Introductionmentioning
confidence: 96%
“…However different results have also been reported [12,14,15]. Most studies on HLA Class II molecules antigens, have shown association with well differentiated thyroid carcinoma [7,9,11,13,16].…”
Section: Introductionmentioning
confidence: 98%
“…[87][88][89]80 In the absence of iodide deficiency, other HLA-linked influences were important for those exposed to other environmental hazards. At least in iodide deficient areas, HLA DR3 appeared to be permissive for nonmalignant transformation.…”
Section: Genetic Factorsmentioning
confidence: 99%